PENGEMBANGAN BAHAN AJAR PEMBELAJARAN BAHASA INDONESIA MATERI TEKS EKSPOSISI BERBASIS KEARIFAN LOKAL PADA SISWA KELAS V SDN SIUMBATU - Nani Kurniawati Bansoe; Mohammad Tahir; Gazali (JS (JURNAL SEKOLAH), 2026)
Abstract: This study aims to develop Indonesian language teaching materials on exposition texts based on local wisdom for fifth-grade students of SDN Siumbatu and to examine their feasibility, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 30 fifth-grade students in the 2025/2026 academic year. Data were collected through observation, interviews, questionnaires, expert validation, and pretest–posttest assessments. The material expert validation result reached 86% and the media expert validation reached 84%, both categorized as highly feasible. Students’ responses showed an average percentage of 89% in the very good category. The effectiveness analysis indicated an increase in the mean score from 62.40 in the pretest to 83.20 in the posttest, with an N-Gain score of 0.55 categorized as moderate. These findings demonstrate that the developed local wisdom-based exposition text teaching materials are feasible, practical, and effective in improving elementary students’ exposition writing skills. The integration of local wisdom makes learning more contextual, meaningful, and relevant to students’ daily lives. Keyword: teaching materials, exposition text, local wisdom, elementary school, ADDIE model Abstrak: Penelitian ini bertujuan untuk mengembangkan bahan ajar pembelajaran Bahasa Indonesia materi teks eksposisi berbasis kearifan lokal pada siswa kelas V SDN Siumbatu serta menguji kelayakan, kepraktisan, dan efektivitasnya. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Subjek penelitian adalah 30 siswa kelas V tahun ajaran 2025/2026. Teknik pengumpulan data dilakukan melalui observasi, wawancara, angket, validasi ahli, serta tes pretest dan posttest. Hasil validasi ahli materi memperoleh persentase 86% dan ahli media 84% dengan kategori sangat layak. Respon siswa terhadap penggunaan bahan ajar menunjukkan persentase rata-rata 89% dengan kategori sangat baik. Hasil analisis efektivitas menunjukkan adanya peningkatan nilai rata-rata dari 62,40 pada pretest menjadi 83,20 pada posttest dengan nilai N-Gain sebesar 0,55 yang berada pada kategori sedang. Temuan ini menunjukkan bahwa bahan ajar teks eksposisi berbasis kearifan lokal yang dikembangkan layak, praktis, dan efektif dalam meningkatkan kemampuan menulis teks eksposisi siswa sekolah dasar. Integrasi kearifan lokal dalam bahan ajar menjadikan pembelajaran lebih kontekstual, bermakna, dan relevan dengan kehidupan siswa. Kata Kunci: bahan ajar, teks eksposisi, kearifan lokal, sekolah dasar, model ADDIE